"...örökös nyomorúságra ide kárhoztatva..." - egy megrekedt lelkészi életpálya Glöckner Jakab lieblingi lelkipásztor élete - Szász Lajos (Délvidéki szemle, 2022)
This case study deals with an unknown rural pastor of the Reformed Church of Hungary. The Rev. Jakab Glöckner served as minister in the german-speaking tiny Reformed congregation of Liebling (Temes County) in the 19th century. The long-lasting service of this minister can be treated as a sample of the stagnated pastoral career. His congregation suffered from a long denominational conflict, which caused at last, that the Reformed congregation ceased to exist. Glöckner tried to change his parish many times, but the circumstances made this impossible for him. Not just his lack of connections and his distance from the leading professional networks of his church caused the halt in his career. His education also shew up severe shortcomings. This study reveals the manifold motives by which the local and higher levels of church administration appreciated the serving pastors.